Initial Reports of the Deep Sea Drilling Project 1975
DOI: 10.2973/dsdp.proc.32.117.1975
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Diagenesis of Volcanic-Rich Sediments from North Pacific Seamounts, DSDP Leg 32

Abstract: Volcanic sandstones were recovered from sites along seamount chains in the North Pacific. Three different modes of origin are proposed for them. The well-rounded, commonly weathered basalt sand and fine gravel from Köko Guyot in the southern part of the Emperor Seamount chain is accompanied by whole and abraded shallow-water fossils, and is epiclastic, reworked at shallow depths. The fine, angular altered hyaloclastite sand from a submarine eruption of the Hawaiian Ridge west of Midway Islands is of turbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, Matter and Gardner (1975) interpret the abundance of shallow-water benthic foraminifers, calcareous green algae, coralline algae, and ooids as indicators of a water depth of less than 4 to 6 meters. On Kökö Seamount, the absence of larger orbitoid foraminifers and the higher proportion of bryozoans to corals, which make up not more than 2 per cent of the sediment, was already noted by Moberly and Keene (1975). They concluded that "the shallow water of Kökδ Guyot during the early Eocene was not typical of the tropics."…”
Section: Environment Of Depositionmentioning
confidence: 96%
“…However, Matter and Gardner (1975) interpret the abundance of shallow-water benthic foraminifers, calcareous green algae, coralline algae, and ooids as indicators of a water depth of less than 4 to 6 meters. On Kökö Seamount, the absence of larger orbitoid foraminifers and the higher proportion of bryozoans to corals, which make up not more than 2 per cent of the sediment, was already noted by Moberly and Keene (1975). They concluded that "the shallow water of Kökδ Guyot during the early Eocene was not typical of the tropics."…”
Section: Environment Of Depositionmentioning
confidence: 96%
“…Cretaceous volcaniclastic deposits are clearly linked to intraplate volcanism (e.g., Viereck et al 1985;Moberly and Keene 1975;Moberly 1981;Kelts and McKenzie 1976;Timofeev et al 1981), mid-ocean ridge systems (Vallier and Jefferson 1981), and Cretaceous oceanic plateaus (Klein 1975;Tarduno et al 1991). Emplacement of bottom-transported density flows from shallow subaqueous and subaerial volcanoes dominated (e.g., Moberly and Keene 1975;Moberly 1981) with only minor fallout components (Tarduno et al 1991). Schlanger et al (1981) suggested that the Cretaceous volcanic pulse caused regional uplift with an amplitude of approximately 1000-2000 m ("Darwin Rise") that brought many sites above the calcite compensation depth and the top of the volcanic structures near seal evel.…”
Section: Low Signal From Intraplate Volcanismmentioning
confidence: 99%
“…Large reef benthic foraminifers were not reported. However, Moberly and Keene (1975) described rounded fragments of calcite spar that were transported to the site, presumably by the turbidity currents that deposited the enclosing volcaniclastic sandstones. We suggest that these spar fragments were derived from eroding reefs coeval with the reef skeletal debris from Sites 462, 165, 315, and 316.…”
Section: Mid-pacific Mountainsmentioning
confidence: 99%